Future Change to Tide‐Influenced Deltas - Jaap H. Nienhuis; A. J. F. (Ton) Hoitink; Torbjörn E. Törnqvist (Geophysical Research Letters)
Abstract Tides tend to widen deltaic channels and shape delta morphology. Here we present a predictive approach to assess a priori the effect of fluvial discharge and tides on deltaic channels. We show that downstream channel widening can be quantified by the ratio of the tide‐driven discharge and the fluvial discharge, along with a second metric representing flow velocities. A test of our new theory on a selection of 72 deltas globally shows good correspondence to a wide range of environments, including wave‐dominated deltas, river‐dominated deltas, and alluvial estuaries. By quantitatively relating tides and fluvial discharge to delta morphology, we offer a first‐order prediction of deltaic change that may be expected from altered delta hydrology. For example, we expect that reduced fluvial discharge in response to dam construction will lead to increased tidal intrusion followed by enhanced tide‐driven sediment import into deltas, with implications for navigation and other human needs.